The Behavioral Implications of a Multi-Individual Bonebed of a Small Theropod Dinosaur - Ibiricu, Lucio Manuel (2013)
Background: Central Patagonia, Argentina, preserves an abundant and rich fossil record. Among vertebrate fossils from the Upper Cretaceous Bajo Barreal Formation of Patagonia, five individuals of the small, non-avian theropod dinosaur Aniksosaurus darwini were recovered. Group behavior is an important aspect of dinosaur paleoecology, but it is not welldocumented and is poorly understood among non-avian Theropoda. Methods/Principal Findings: The taphonomic association of individuals from the Bajo Barreal Formation and aspects of their bone histology suggest gregarious behavior for Aniksosaurus, during at least a portion of the life history of this species. Histology indicates that the specimens were juvenile to sub-adult individuals. In addition, morphological differences between individuals, particularly proportions of the appendicular bones, are probably related to body-size dimorphism rather than ontogenetic stage. Conclusions/Significance: Gregarious behaviour may have conferred a selective advantage on Aniksosaurus individuals, contributing to their successful exploitation of the Cretaceous paleoenvironment preserved in the Bajo Barreal Formation. The monospecific assemblage of Aniksosaurus specimens constitutes only the second body fossil association of small, coelurosaurian theropods in South America and adds valuable information about the paleoecologies of non-avian theropod dinosaurs, particularly in the early Late Cretaceous of Patagonia.